2022
DOI: 10.1097/dcr.0000000000002191
|View full text |Cite
|
Sign up to set email alerts
|

Transanal Suture Mucopexy for Hemorrhoids

Abstract: BACKGROUND: Core factors involved in the treatment of hemorrhoids include the engorgement of hemorrhoids, prolapse, recurrence, and pain. OBJECTIVE:The goal of this study was to assess the safety, pain, and efficacy of the transanal suture mucopexy for the treatment of hemorrhoids. DESIGN:This was a retrospective study over a 13-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The inclusion criteria are as follows [11]: (1) Age of 18 to 75 years, with no limitation according to sex; (2) grade II-III internal haemorrhoids with accompanying symptoms, such as bleeding, prolapse, or itching; (3) conservative treatment for grade II-III internal haemorrhoids such as diet regulation and drugs has proven ineffective; (4) patients unwilling to undergo haemorrhoidectomy. The exclusion criteria are as follows [12]: (1) Grade IV haemorrhoids, mixed haemorrhoids, or external haemorrhoids; (2) internal haemorrhoids accompanied by incarceration, thrombosis, erosion, or infection; (3) patients with severe systemic diseases who cannot tolerate endoscopic treatment; (4) patients with perianal infectious diseases or anal stulae; (5) patients with active in ammatory bowel disease; (6) patients with coagulation dysfunction or using anticoagulants; (7) pregnant women.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria are as follows [11]: (1) Age of 18 to 75 years, with no limitation according to sex; (2) grade II-III internal haemorrhoids with accompanying symptoms, such as bleeding, prolapse, or itching; (3) conservative treatment for grade II-III internal haemorrhoids such as diet regulation and drugs has proven ineffective; (4) patients unwilling to undergo haemorrhoidectomy. The exclusion criteria are as follows [12]: (1) Grade IV haemorrhoids, mixed haemorrhoids, or external haemorrhoids; (2) internal haemorrhoids accompanied by incarceration, thrombosis, erosion, or infection; (3) patients with severe systemic diseases who cannot tolerate endoscopic treatment; (4) patients with perianal infectious diseases or anal stulae; (5) patients with active in ammatory bowel disease; (6) patients with coagulation dysfunction or using anticoagulants; (7) pregnant women.…”
Section: Study Populationmentioning
confidence: 99%
“…We mainly focused on white blood cell (WBC) and neutrophil (NEUT) counts among the blood tests. Anal pain intensity was quanti ed by the Visual Analogue Scale (VAS), with scores on a scale of 0-10, where 0-3 indicates mild pain, 4-6 indicates moderate pain, 7-9 indicates severe pain, and 10 indicates excruciating pain [12].…”
Section: Safety Measures (1) Primary Outcome Measures: Postoperative ...mentioning
confidence: 99%
“…Genetic predispositions also play a role, suggesting that familial history can be indicative of one likelihood to develop this ailment. [7,8] Severe cases of hemorrhoidal disease present a major clinical concern, often characterized by excruciating pain, rectal bleeding, and prolapsed hemorrhoidal tissue, which can severely impede normal bowel function and significantly deteriorate the quality of life of the affected individuals. [9–11]…”
Section: Introductionmentioning
confidence: 99%
“…Genetic predispositions also play a role, suggesting that familial history can be indicative of one likelihood to develop this ailment. [7,8] Severe cases of hemorrhoidal disease present a major clinical concern, often Written informed consent for publication was obtained from all patients and their families included in this retrospective study.…”
Section: Introductionmentioning
confidence: 99%
“…TSM was first published in 2012 [1]. A recent large multicentric study has shown the success rate of 98.6% in 5541 patients with a median follow‐up of 6 years [2]. There is minimal pain after the procedure (analogue score 1–2 in 97.8% and 2–3 in 2.2% patients) [2].…”
mentioning
confidence: 99%